Predictors of the acquisition and portability of transferable skills: A longitudinal portuguese case study on education. - Rocha, Magda (2014)
The basis for this longitudinal study was to find the predictors of transferable skills acquisition and portability among university sophomore students. The method employed was the path analysis using as variables: (i) the theoretical framework of transferable skills representations (Evers & Rush, 1996) in the freshman and sophomore years, (ii) the developmental dimensions of Career adaptability and Vocational development (Savickas, 2001, 2002, 2005, 2009), and, (iii) the grades for Project I and Project II (curricular units specially developed for the acquisition of groups of transferable skills in the first and second years of Economics and Management program at the Catholic University of Porto [herein referred to as Catholic University of Porto]. The criteria used were the grades from two second-year curricular units (Business Law and Statistics). The objective was to observe the impact of other dimensions on actual skills acquisition, considering the influence of the former on the grades of Business Law and Statistics as an indicator of portability of the transferable skills acquisition. All participants were male and female students at the Catholic University of Porto, Faculty of Economics and Management, between 18 and 25 years of age (M=18.53, SD=1.37) at the first assessment (N=193). Results suggest that Project I grades are the best predictor of both Business Law and Statistics grades. However, results also reveal that student’s representations of their transferable skills measured at the first and the second year are mediated by Career adaptability measured at the second year. Results are discussed based on the aforementioned frameworks.